Microcirculation and haemodynamics after infraclavicular brachial plexus block using adrenaline as an adjuvant to lidocaine: a randomised, double‐blind, crossover study in healthy volunteers. (7th August 2019) - Holmberg, A.; Ho, A. V.; Fernand, D.; Toska, K.; Wester, T.; Klaastad, Ø.; Drægni, T.; Sauter, A. R.
Summary: We evaluated the effect of adrenaline on human skin microcirculation (nutritive and sub‐papillary) and systemic cardiovascular variables after it was added to lidocaine in infraclavicular brachial plexus blocks. Twelve healthy, non‐smoking male volunteers were included, each attending two study sessions 2 weeks apart, and they were studied using a crossover design. In both sessions, they received an ultrasound‐guided infraclavicular brachial plexus block in the non‐dominant arm with 0.4 ml.kg −1 lidocaine, 15 mg.ml −1 with or without adrenaline 5 μg.ml −1 . Microcirculation was assessed by laser Doppler fluxmetry (sub‐papillary blood flow), capillary video microscopy (nutritive blood flow) and continuous temperature measurements. Heart rate and arterial pressure were recorded continuously and non‐invasively. Median (IQR [range]) sub‐papillary blood flow increased substantially 30 min after the brachial plexus block, from 8.5 (4.4–13.5 [2.9–28.2]) to 162.7 (111.0–197.8 [9.5–206.7]) arbitrary units with adrenaline (p = 0.017), and from 6.9 (5.3–28.5 [1.8–42.1] to 133.7 (16.5–216.7 [1.0–445.0] arbitrary units without adrenaline (p = 0.036). Nutritive blood flow (functional capillary density, capillaries.mm −2, measured at the dorsal side of the hand) decreased in the blocked extremity when adrenaline was used as adjuvant, from median (IQR [range]) 45 (36–52 [26–59]) to 38 (29–41 [26–42]), p = 0.028, whereas no significant change occurred without adrenaline. Median finger skin temperature (°C) increased by 44% (data pooled) with no significant differences between the groups. No significant changes were found in the systemic cardiovascular variables with or without adrenaline. We conclude that lidocaine infraclavicular brachial plexus blocks caused an increase in skin sub‐papillary blood flow. The addition of adrenaline produced stronger and longer lasting blocks, but decreased the nutritive blood flow.